Anna Fitzgerald's Existence Reflected At Jodi Picoult's My Sister's Keeper (2004): An Existentialist Approach - Ningsih, Eka Naning Widia, Dr.Phil. Dewi Chandraningrum, S.Pd., M.Pd, Titis Setyabudi, S.S. M. Hum (2014)
This study is about the Existence of Anna Fitzgerald in My Sister's Keeper novel. The problem of this study is the struggle of a child that wants to get her existence in her family and society. The object of the study is My Sister's Keeper novel by Jodi Picoult. This research is using of existentialist approach. The study belongs to qualitative research. There are two types of data source, namely primary data and secondary data. The secondary data is other material related to the study. The result of the study shows the following conclusion. irst, based on structural analysis, it shows that each elements are connected to each other forming unity. Second, based on existentialist analysis Jodi Picoult wants to show the struggle of Anna Fitzgerald to gets her existence as a child in her family and society.